Inhibition of Lipid Peroxidation of Kiwicha (Amaranthus caudatus) Hydrolyzed Protein Using Zebrafish Larvae and Embryos - Vilcacundo, Ruben (2018)
Fil: Vilcacundo, Ruben. Technical University of Ambato. Faculty of Foods Sciences and Engineerin. Laboratory of Functional Foods; Ecuador.